Docosahexaenoic Acid (DHA), an Important Fatty Acid in Aging and the Protection of Neurodegenerative Diseases - Valenzuela, Rodrigo Wladimir; Sanhueza, Julio; Valenzuela, Alfonso (Journal of Nutritional Therapeutics, 2012)
Docosahexaenoic acid (DHA) is a fatty acid essential for the proper development and functioning of the nervous and visual system. DHA is found in significant concentrations in the phospholipids of neuronal membranes. DHA is provided by the mother during the fetal and early infancy life, during pregnancy and through breastfeeding. Given the importance of an adequate supply of the fatty acid to the newborn, it has been suggested DHA supplementation to the mother before and during the pregnancy and also during the breastfeeding period. In the recent years, research from different scientist have established that DHA has an important role in the development of the nervous system, as well as having an important key role in the preservation of this tissue, especially during aging and in some neurodegenerative diseases, such as Alzheimer’s disease, Multiple Sclerosis and Parkinson’s disease. DHA may preserve the integrity and the neuronal viability against different metabolic insults and/or cytotoxic events, among which inflammation and oxidative stress are the most relevant. The neuroprotective effects of DHA in neural tissue are mediated by a metabolic derivative, known as neuroprotectin D-1. This molecule may respond to aggression having anti-inflammatory, antiapoptotic and even neuroregenerative effects, which may contribute to preserve the proper neuronal viability as well as the health and function of the nervous system. This review discusses different evidences about the neuroprotective effect of DHA, during aging and against some neurodegenerative diseases, highlighting the important role of the proper nutrition in this protection